(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role of the Uzbek language in the life of our people, its invaluable significance in expressing our national values, and its place in the development of society. Our mother tongue is highlighted not only as a means of communication, but also as an important factor in preserving spiritual heritage, understanding national identity, and transmitting cultural wealth to future generations. In recent years, discussions have been based on reforms in language policy and the education system, government programs, and scientific research aimed at developing the language. The impact of modern technologies, electronic dictionaries, linguistic platforms, and information systems on the process of language learning is also examined. Special attention is paid to raising the prestige of the Uzbek language worldwide, expanding its scope of use in the international arena, and promoting it widely in scientific and artistic literature.